Arah Penataan dan Pengembangan Konsep Waterfront City Pada Objek Wisata Pantai Soge Pacitan (Jurnal Ekonomi Bisnis dan Akuntansi, 2021)
Soge Beach is a tourist attraction that has many tourist attractions. However, the use of space in it is still not structured and neatly arranged. This causes a decrease in tourist attraction, the quality of natural resources and the existing ecosystem. The concept of a waterfront city is a concept of structuring a waterfront area that emphasizes the principle of sustainability. The purpose of this study is to provide an overview of the direction of the arrangement and development of the waterfront city concept at the Soge Pacitan Beach tourist attraction. The research method used is a qualitative descriptive method to explain, explain, describe, describe, and answer the problems at Soge Beach in more detail. The results obtained are the spatial arrangement of the Soge Beach waterfront directed at land use, building planning, circulation and parking, open space, pedestrian paths, supporting activities, marking and preservation and conservation. As for the development of the waterfront, it is directed towards infrastructure, architecture, facilities and tourism activities. With these results, it is hoped that it will have an impact on the new face of the Soge Beach tourism object so that it can encourage rapid economic growth. Pantai Soge merupakan objek wisata yang memiliki banyak dari tarik wisata. Namun, pemanfaatan ruang di dalamnya masih belum terstruktur dan tertata rapi. Sehingga menyebabkan turunnya daya tarik wisara, kualitas sumber daya alam dan ekosistem yang ada. Konsep waterfront city merupakan konsep penataan kawasan terpian air yang mengedepankan prinsip keberanjutan. Penelitian ini bertujuan untuk menjelaskan dan menggambarkan arah penataan dan pengembangan konsep waterfront city pada objek wisata Pantai Soge Pacitan. Metode penelitian yang digunakan yaitu metode deksriptif kualitatif untuk menerangkan, menjelaskan, menggambarkan, melukiskan, dan menjawab permasalahan di Pantai Soge secara lebih rinci. Hasil penelitian yang diperoleh yaitu penataan ruang waterfront Pantai Soge diarahkan pada tata guna lahan dan bangunan, sirkulasi dan parkir, ruang terbuka, jalur pejalan kaki, aktivitas pendukung, penandaan serta preservasi dan konservasi. Sedangkan untuk pengembangan waterfront, diarahkan infrastruktur, arsitektur, fasilitas dan aktivitas wisata. Dengan hasil tersebut, diharapkan dapat memberikan dampak bagi wajah baru ovjek wisata Pantai Soge sehingga mampu mendorong pertumbuhan ekonomi dengan cepat.